Casas Grandes and its hinterland : prehistoric regional organization in northwest Mexico - Whalen, Michael E. (Book collections on Project MUSE., 2001)
"Michael E. Whalen and Paul E. Minnis have worked extensively in the Casas Grandes area and now offer new research arguing that it was not as similar to the highly developed complex societies of Mesoamerica as has been thought. In the first book of its kind in 25 years, the authors analyze settlement pattern data from more than 300 communities in the area surrounding Casas Grandes to show that its Medio period culture was a local development."--Jacket.